ICT and agricultural development: the impacts of information and communication-technology on agriculture - Amaral, Luiz Fernando do (2017)
Within a context of continuous population and economic growth, the future projections for agricultural products\' demand is impressive. At the same time, agriculture already exercises significant pressure on natural resources. As a consequence, the world needs to produce higher agricultural volumes while limiting agriculture\'s impacts on the environment. This thesis evaluates whether empirical indications exist that demonstrate how Information and Communication Technology (ICT) infrastructure development and usage could impact the sustainable development of agriculture. Drawing from the empirical literature on infrastructure\'s impacts on development, two statistical models are created. The first analyses impacts of Internet and mobile usage on cereal yields at a country level using Fixed Effects Panel Regression for 212 countries in five 5-year periods, from 1990 to 2014. The second uses a Propensity Score Matching Model to evaluate how the installation of 3G technology during the period between 2005 and 2009 in Brazilian municipalities located in the Amazon region affected deforestation. Based on the methodology and datasets used, results indicate that the growth of Internet users could have a positive impact on cereal productivity in a country. Results for mobile device users are inconclusive. Finally the second models indicate that municipalities in which 3G technology was installed had lower deforestation rates than similar municipalities lacking 3G technology.